The Whistleblowing Directive: Key aspects of its transposition into Spanish law - José Caro Catalán (Revista Brasileira de Direito Processual Penal)
This paper analyses the key aspects of the imminent transposition into Spanish law of Directive (EU) 2019/1937 of the European Parliament and of the Council of 23 October 2019 on the protection of persons who report breaches of Union law. As a starting point, it provides a contextualisation of the phenomenon of whistleblowing at the global level. Then, the essential content of the Directive is addressed, going deeper into the internal and external whistleblowing channels. Finally, the key aspects of its transposition into Spanish law are addressed. To carry out this last section, the author makes use of the public consultation on the transposition of the Directive proposed by the Ministry of Justice on 7 January 2021, as well as some of the contributions made during this process by stakeholders.